Late Jurassic Structural Deformation and Late Cenozoic Reactivation of the Southern Junggar Fold-And-Thrust Belt, NW China - Ma, Delong; Yuan, Jianying; Sun, Yanpeng; Wang, Hongbin; He, Dengfa; Wang, Yanjun; Pan, Shuxin; Cui, Jian (Frontiers in Earth Science, 2021)
Because of the influence of the far field effect of the collision between Euro-Asian and India plates during Late Cenozoic, the Tian Shan orogenic belt underwent intense reactivation, forming the Southern Junggar fold-and-thrust belt (SJ-FTB) to the north and Kuqa fold-and-thrust belt to the south. Most of the previous researches focused on the deformation features and mechanism during Late Cenozoic. However, little research has been done on deformation features and mechanism during Late Jurassic. In this paper, we conducted geometric and kinematic analysis of seismic profiles and outcrop data to reveal the Late Jurassic deformation characteristics in SJ-FTB. Furthermore, we carried out sandbox modeling experiments to reproduce the regional structural evolution since Early Jurassic. Angular unconformity between Cretaceous and Jurassic is well preserved in Qigu anticline belt. This unconformity also exists in the Huoerguosi-Manasi-Tugulu (HMT) anticline belt, which is the second fold belt of the SJ-FTB, indicating that HMT anticline belt started to active during Late Jurassic. The Qigu anticline belt reactivated intensively during Late Cenozoic and the displacement was transferred to HMT anticline belt along Paleogene Anjihaihe Formation mudstone detachment. Therefore, the present-day SJ-FTB forms because of the two-stage compressional deformation from both Late Jurassic and Late Cenozoic (ca. 24Ma).